Moringa oleifera leaf ethanol extract ameliorates lead-induced hepato-nephrotoxicity in rabbits - Nancy B Mohamed; Amira H Mohamed; Nashwa A Abu-Aita; Soad M Nasr; Somia A Nassar; Kawkab A Ahmed (Asian Pacific Journal of Tropical Biomedicine, 2020)
Objective: To evaluate the effect of Moringa oleifera leaf ethanol extract as an adjunct treatment on lead acetate induced hepato- nephrotoxicity in rabbits. Methods: Thirty-six male New Zealand White rabbits were assigned into two main groups. The first group (14 rabbits) served as normal control. The secondgroup (22 rabbits) was administered orally with lead acetate at a dose of 40 mg/kg/day, 5 days/week for 8 weeks. At the 4th and the 8th week of treatment, 6 animals (3 animals at each period) of the second group were sacrificed while the remaining animals (16 rabbits) were assigned randomly into 2 subgroups (8 rabbits each): treated and non-treated. The first subgroup was orally given 1 mL phosphate-buffered saline for further 4 weeks while the second subgroup was administered orally with Moringa oleifera leaf ethanol extract at a dose of 400 mg/kg/day for the same period. Blood samples were collected to determine hematological and serum biochemical indices. Tissue specimens were collected from the liver and kidney for evaluation of the oxidant/antioxidant markers and for histopathological examinations. Results: Lead acetate exposure decreased the mean body weight gain, hematocrit, hemoglobin, mean corpuscular volume, and lymphocytes count. Moreover, it markedly increased counts of monocytes and platelets, serum enzyme activity, levels of creatinine, total cholesterol, triglycerides, and low-density lipoprotein cholesterol. Malondialdehyde level was markedly increased while the reduced glutathione content was significantly decreased in liver tissue of lead intoxicated-rabbits. Histopathological alterations were also noticed in the liver and kidney of lead intoxicated rabbits. Moringa oleifera leaf ethanol extract significantly improved hematological and serum biochemical parameters and histopathological structure of the liver and kidney. Conclusions: Moringa oleifera leaf ethanol extract ameliorates hemato-biochemical and histopathological alterations caused by lead acetate and improveshepatic and renal ...